STATUS SOSIAL KELUARGA, LITERASI KEUANGAN TERHADAP MANAJEMEN KEUANGAN INDIVIDU DAN LIFESTYLE - Budhiartha, I Nyoman; Wibowo, Agung Edy; A. Nasution, M. Nur.; L. Tobing, Vargo Christian,; Cahayani, Kartika (JURSIMA, 2024)
The social status of a family plays a crucial role in shaping a student's ultimate career aspirations as an individual, as does financial literacy, which an individual acquires from their parents or through learning and experience. A family's social status naturally influences whether a child, as an individual, has better access to financial education or otherwise. Families with a higher social status will certainly provide different opportunities compared to those of lower economic standing. Similarly, strong financial literacy can help individuals manage their personal finances effectively. In this era of disruptive technology, a family's socioeconomic status, financial literacy, and individual financial management models can all impact one's lifestyle. This study aims to analyze the influence of a family's socioeconomic status, financial literacy, and individual financial management on lifestyle. The respondents of this study numbered 123. The results indicate that family social status affects individual financial management, financial literacy affects individual financial management, family social status affects lifestyle, financial literacy affects lifestyle, and individual financial management affects lifestyle. Additionally, individual financial management mediates the relationship between family social status and lifestyle, as well as between financial literacy and lifestyle. Keywords: Family social status, Financial literacy, Individual financial management, Lifestyle